Bipolar to unipolar conversion in superjunction MOSFETs during resonant switching - H. Kang; F. Udrea (Power Electronic Devices and Components, 2024)
Superjunction MOSFETs have been one of the promising switching components for realizing resonant converters. In spite of the numerous studies about the resonant converters in power electronics, the detailed current flow in the device has been still unclear, especially for the inner-current circulation between the body diode and the MOSFET. By employing five-terminals on the superjunction MOSFET, mixed-mode half-bridge resonant converter is simulated. During the turn-on of the MOSFET, the gate charging current flows into the drain-to-source capacitance to form a built-in depletion of the pillars. In the case of the turn-off, the source current reversely flows across the channel with a slightly negative drain-to-source bias and diverts to the gate discharging current.